Thermal ecology of Microlophus occipitalis (Sauria: Tropiduridae) in the Plain Dry Forest of Tumbes, Peru - Jordán A., Juan C. (2012)
The thermal ecology of Microlophus occipitalis Peters 1871 in the plain dry forests of Tumbes (northewestern Peru) was studied. Mean body temperature was 36.1 ± 1.8 ºC, similar to body temperatures exposed by Microlophus peruvianus in northern Peru. There were no differences between body temperature and degree of thermoregulation of males and females, due to a possible association to their social structure and microhabitat use. Air and substrate temperature affects the body temperature of Microlophus occipitalis, where air temperature accounts for a significant proportion of body temperature variation. We suggest more detailed studies on this lizard species, especially under climate change scenarios in northwestern Peru.